Respuesta :
Step-by-step explanation:
equatiin of line L1;y-y1=m(x-x1)
m=y2-y1/x2-x1=-1-3/3-0=-4/3
the two lines are parallel
m1=m2
L2;y-y1=m(x-x1)
y-2=-4/3(x-(-3)
3y-6=-4x-12
3y+4x=-6 is equation of parrallel lines.
The equation of the line with the given conditions is:
[tex]4x + 3y = -6[/tex]
The equation of a line is given by:
[tex]y = mx + b[/tex]
In which:
- m is the slope, which is the rate of change.
- b is the y-intercept, which is the value of x when y = 0.
If two lines are parallel, they have the same slope.
The slope is the change in y divided by the change in x. Parallel to a line with points (0,3) and (3,-1), thus:
[tex]m = \frac{-1 - 3}{3 - 0} = -\frac{4}{3}[/tex]
Thus:
[tex]y = -\frac{4}{3}x + b[/tex]
Passes through point (-3,2), which means that when [tex]x = -3, y = 2[/tex], and this is used to find b.
[tex]2 = -\frac{4}{3}(-3) + b[/tex]
[tex]4 + b = 2[/tex]
[tex]b = -2[/tex]
Then
[tex]y = -\frac{4}{3}x - 2[/tex]
Placing it into standard form:
[tex]3y = -4x - 6[/tex]
[tex]4x + 3y = -6[/tex]
A similar problem is given at https://brainly.com/question/16302622